Use of oblong socket in hip revision surgery - Cameron, H U; Smula, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1999)
A 2 to 8 year follow up has been conducted in the use of an ingrowth noncemented oblong acetabular component used in hip revision surgery. To date no loosening and no significant migration has occurred. These intermediate results are promising and warrant further study of this implant. Key words: S-ROM, THR, revision surgery, oblong cup.